PENGARUH VIRAL MARKETING TERHADAP MINAT BELI PRODUK MOTHER OF PEARL - Silvia Justiana; Lingga Yuliana (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the effect of viral marketing on buying interest in mother of pearl product on the Tik Tok application. Novelty in this research where case studies used have not been found in partial and simultaneous correlations. The method applied in this study is a quantitative descriptive method.  Research data comes from primary data. Taking. Sampling is taken by purposive sampling with the criteria that the respondent has never bought a mother of pearl product.  Male and Female respondents were involved in this study with an age range of 17-55 years.Determination of the number of samples using the slovin sampling formula. Respondents involved in the study were 100. The data testing uses multiple linear regression analysis with SPSS version 25. The Likert scale is used to determine the answers by respondents. Based on the research results, it showed viral marketing variable have a positive and significant effect partially on the purchase intention variable. If Viral Marketing increased then purchase intention buy interest in mother of pearl products.